Pola Implementasi Program Kursus Bahasa Inggris Berbasis Masyarakat dalam Meningkatkan Kompetensi Warga Belajar - Ratna Ayu Komalasari; M A Rizka; Wayan Tamba (Universitas Pendidikan Mandalika, 2020)
This study aims to describe the pattern of implementing community-based English course programs in an effort to improve the competence of learning citizens at the FLI Rinjani Mataram institution. This research is a descriptive study with a qualitative approach. The subjects of this study were instructors, learning citizens, and administrators of the FLI Rinjani Mataram institution. Researcher is the main instrument which is assisted by observation guidelines, interview guidelines, and documentation guidelines. The technique analyzes the research data uses qualitative data analysis with interactive methods. The results showed that the implementation pattern of the English course program at FLI Rinjani Mataram was carried out with 20 meetings for 3 months held in the classroom and supported by the implementation outside the classroom. The English language course program manager organizes course activities through the stages of course program management and training such as planning, implementation, evaluation and follow-up. The result of the implementation of the English language course program is that learning citizens are able to acquire the desired skills in the field of English with the services and supporting media provided by the institution so that learning citizens are able to improve their English competency.